The Value Of Fanily Life in the Film A Million Darling For Him (Jhon Fiske Semiotic Analysis) - Rizki Muhammad Akbar (Journal of Social Science and Humanities, 2023)
The family is the first and foremost place for the growth and development of children. If the atmosphere in the family is good and fun, then the child will grow well too. Otherwise it will hinder the growth of the child. The role of parents in the family is very important. Fathers tend to be in the public sector (earning a living). It is widely developed in society that single parent men cannot take care of their children properly and because they are busy making a living for their children, this research is entitled "The Value of Family Life in the Film A Million Sayang Untuknya". The purpose of this analysis is to find out the message of the value of life in the family. The theory used to analyze the research is mass communication theory, and Jhon Fiske's semiotic analysis, namely 3 stages of reality level, representative level and ideological level. The method used is a qualitative research method. The results showed that there were 10 scene pieces presented from the values of family life in this film. This study resulted in conclusions, namely 1) The level of reality through the appearance of a million affectionate film player for him shows simplicity. 2) The level of representation is a scene that contains taking pictures and dialogue about the value of life from the figure of the father. 3) The ideology level, based on the description at the level of reality and representation, shows that the ideology of the film is Individualism.